(untitled) (Ciudades, 2017)
This article reflects on the notion of metropolitan areas in the city of Grenada region in order to strengthen the cohesion and values that structure the territory. The framework of the study are the three metroplitan axes of Grenada to Guadix, Loja and Motril, being the areas with the greatest potential for transformation, trade and development.The potential value centers move to multiple locations and need to be analyzed and given a new urban meaning, richer in relationships. It should draw this unique field of centralities with useful maps showing its strategic location and qualities inherent to the inclusion of open programs and changing. This raises the need to articulate the urbanized and extensive territory as a network of multiple beams or intersections through exploration other focal places, the analysis of its disposition and distribution, shifts, repetitions, proximity, etc